Tempo de permanência do curativo após mamoplastia redutora: influência na colonização, na infecção da ferida operatória e na opinião das pacientes - Veiga Filho, Joel [UNIFESP] (2010)
Background: There is controversy in the literature regarding the treatment of surgical wounds, which includes different approaches to wound management, such as “not to dress the wound” to “leave the dressing in place for 24-48 hours” or “until sutures are removed”. Objective: To evaluate the effect of the length of time the dressings were left in place after reduction mammaplasty on skin colonization, surgical site infection, and patient opinion. Methods: Seventy patients undergoing reduction mammaplasty were randomly divided into two groups: group PO1 (dressing was removed on the first postoperative day) and group PO6 (dressing was removed on the sixth postoperative day). Skin colonization was detected by culture of samples collected at predefined time points. Surgical site infections were classified according to the guidelines of the Centers for Disease Control and Prevention (CDC). Patient satisfaction was assessed on postoperative day 13. Results: A larger number of colony-forming units were measured in group PO1 on postoperative day 6. Nine (12.9%) patients had surgical site infection (seven from group PO1, and two from group PO2). In group PO1, 66% of the patients chose to keep the dressing for one day, while 83% of the patients in group PO6 chose to keep the dressing for six days. Conclusions: Higher colonization levels were observed in group PO1 on the sixth postoperative day. There was no difference in surgical site infection between groups. Most of the patients chose to keep the dressing in place for six days postoperatively, and felt it was safer.